EVALUATION OF A SAFER MALE CIRCUMCISION TRAINING PROGRAMME FOR NDEBELE TRADITIONAL SURGEONS AND NURSES IN GAUTENG, SOUTH AFRICA: USING DIRECT OBSERVATION OF CIRCUMCISION PROCEDURES - Peltzer, K.; Kanta, X.; Banyini, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The aim of this study was to assess the safety of traditional male cirÂ¬cumcision practices among Ndebele traditional surgeons following a five days training by direct observation of circumcision procedures. The sample included eight Ndebele traditional surgeons and traditional nurses and 86 initiates (abakhwetwa) from two districts in Gauteng province in South Africa. A structured observations tool was administered by a trained research doctor during circumcisions and (wound) care of the initiates of the trained traditional surgeons. Results indicate that from the observations of 86 traditional male circumcisions a high number (37%) of adverse events were recorded (excessive bleeding, excessive skin removed and damage to the penis) and in six cases the use of one instrument for the circumcision was observed. Before scaling up and/or considering integration traditional male circumcision services into medical male circumcision services in South Africa, a careful strategy to minimize unnecessary morbidity, and fundamental improvements on current traditional male circumcision techniques, are required. In addition, legislation and control of traditional male circumcision in Gauteng province, where the study took place, are recommended to make traditional male circumcision safer and to prevent adverse events to happen.